Mengoptimalkan Penggunaan Teknologi Dalam Pendidikan Islam - Mardiah Astuti; Herlina, Herlina; Ibrahim, Ibrahim; Miftahur Rahma; Siska Salbiah; Ima Jumratus Soleha (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This article on Optimizing the Utilization of Technology in Islamic Education was written with the aim of forming good morals and morals in individuals. This study was conducted using two methods, namely a qualitative survey and literature review through a review of previous studies whose subject matter is of course related to the title of this article. Character education is very important for someone, because good character will form a good and moral person. Character learning naturally forms a person's character based on what is learned, so that the character remains in it and even forms an identity in the future. In the current era of modernization, character education can be achieved through Islamic learning. So that someone even though living in the era of globalization can preserve Islamic values ​​that are rooted within him.